Simulation of the thermal state of the premises with the heating system «Heat-insulated floor» - Сотник, Микола Іванович; Хованський, Сергій Олександрович; Гречка, Ірина Павлівна; Панченко, Віталій Олександрович; Максимова, Марія Олександрівна (Eastern-European Journal of Enterprise Technologies, 2015)
Application of computer numerical simulation of aerodynamic and heat and mass transfer processes in premises with a radiant heating system "heat-insulated floor" using the software package ANSYS CFX is considered. The main objective of the research is to improve the energy efficiency of thermal energy in premises based on the analysis of their thermal modes. As the object of research, thermodynamic parameters of the thermal state of the premises with a radiant heating system "heat-insulated floor" were selected. The results of simulation of the thermal state of premises allow to carry out a study of the influence of non-stationary processes in the internal volume of premises on the overall thermal state and obtain analytical dependencies of changes in the thermal state parameters of premises on the time of its heating. The research results can be applied by energy auditors in the field of power engineering to assess compliance with the comfort conditions in the premise, analyze its thermal state, evaluate the effectiveness of various energy-saving measures.